What factors affect the methodological and reporting quality of clinical practice guidelines for osteoporosis? Protocol for a systematic review - Fang, Peng-Zhong (Medicine (Baltimore), 2020)
BACKGROUND: Osteoporosis is a disease with a high prevalence and low treatment rate, which poses a serious threat to the lives of patients and brings a heavy economic burden. Clinical practice guidelines (CPGs) provide vital guidance for disease management. Up to now, different countries, regions, and organizations have issued a certain number of CPGs for osteoporosis, but the recommendations in different guidelines are inconsistent. This protocol plans to evaluate the quality of the CPGs for osteoporosis and then make a comparative analysis of the recommendations in the CPGs. METHODS: Several databases including PubMed, Web of Science, Embase, and Cochrane Library, as well as the official website of relevant organizations will be searched. Screen and data extraction will be performed by two reviewers independently, and the third reviewer help to resolve the divergence between them. Using the AGREE II instrument and RIGHT checklist to assess the methodological and reporting quality of the CPGs. The extracted recommendations, including but not limited to screening, diagnosis, evaluation and treatment, will be summarized and analyzed, and the results will be presented in tabular form. Bubble charts will be used to show quality differences between CPGs and to describe the correlation between methodological and reporting quality through regression analysis. Excel, EndnoteX9 and SPSS 25.0 will be used. RESULT: To evaluate the advantages and disadvantages of the existing CPGs of osteoporosis and analyze the similarities and differences between the recommendations, the results will be published in a peer-reviewed journal. CONCLUSION: This study will provide systematic evidence for existing CPGs of osteoporosis and to provide a reference for CPGs users. PROTOCOL REGISTRATION: INPLASY 202070031.